SEBARAN TINGKAT KAPASITAS WILAYAH PESISIR BAGIAN BARAT KABUPATEN BULELENG TERHADAP ANCAMAN PENINGKATAN MUKA AIR LAUT - Eka Putra, I Wayan Krisna (Media Komunikasi Geografi, 2018)
This study aims to describe the distribution of the capacity level the coastal area of west Buleleng Regency from the threat of sea level rise and to know the ratio of the capacity level. The subjects in this study are village officials and staff BPBD Buleleng Regency, while the object of the research is level of capacity. The phenomenon described in this research is distribution of capacity level of coastal area in west Buleleng Regency. Stages conducted in this study consisted of data collection, weighting, determining the level of capacity until finally mapping the level of capacity. data analysis technique that used is qualitative descriptive analysis combined with spatial comparative analysis based on Geographic Information System (GIS) which is aimed to analyze comparison of capacity level among villages in coastal area. The results show that the distribution of the capacity of all coastal areas in west Buleleng Regency is the medium category. Assessments of capacity level indicate a lack of capacity indicators for several villages, particularly on the availability of threat maps and early warning systems. Therefore it is necessary to socialize the document of disaster study which has been made by BPBD of Buleleng Regency.